Metodyka prowadzenia badań nad zagadnieniem przywództwa - Wiśniewska-Szałek, Agata (Methods of carrying out research into the issue of leadership, 2006)
The subject discussed in this paper is the methodology of carrying out research into the issue of leadership as the theory evolved. The author points out various ways of analyzing characteristics, behaviour and references of leadership. They are based on some specific examples, beginning with the oldest theories of characteristics, going on through behavioural and situational theories, finally ending with those practised nowadays.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 141-152